Psychological Distress Model Among Iranian Pre-Hospital Personnel in Disasters: A Grounded Theory Study - Azizi, Maryam; Ebadi, Abbas; Ostadtaghizadeh, Abbas; Dehghani Tafti, Abbasali; Roudini, Juliet; Barati, Mohammad; Khankeh, Hamid Reza; Bidaki, Reza (Frontiers in Psychology, 2021)
Objective: Prehospital Personnel (PHP) who work in disasters under extreme pressure, uncertainty, and complex situations are victims of the disasters themselves, and there is a link between experiencing such incidents and mental health problems. Because most studies focus on the injured and less on the psychological issues of PHP, Therefore, the present study aimed to develop a model to provide relief for PHP in disasters from the psychological perspective. Methods: A Grounded theory methodology recommended by Corbin 2015 was employed Prehospital Personnel (n = 24) participated in a semi-structured interview between July 2018 to May 2020. Results: In the analysis of pre-hospital staff interviews, three main themes were extracted included providing relief with struggle (complexity of incident scenes, command- organizational and occupational challenges), psychological distress (psychological regression and psychological empowerment), and consequences (resilience and job burnout). Seven categories and 22 subcategories were explored from our data via the grounded theory approach Conclusions: PHP managed psychological distress with two approaches: psychological self-empowerment and regression, which resulting in resilience and burnout, respectively. However, due to lack of enough support, this resilience was short-term, turned into burnout over time, and affected the structural factors again as a cycle.